The addition of acetic acid or ethanol to orally taken aluminum salt solution enhanced its availability and then induced toxic effects - Hilmy, Mehdi I.; Alhiti, Sadiq M. A.; Alhabib, Omar AM.; Hilmy, Omar M. (Journal of the Faculty of Medicine Baghdad, 2010)
Background:Aluminum (Al) intoxication was initially reported in patients undergoing hemodialysis and then was linked to Alzheimer’s disease. Man usually is exposed to Al containing antacids, vaccines or foods cooked in Al utensils. The assumption of ingesting sour juices as acetic acid or ethanol may affect favorably the degree of Al absorption is justified when taken in conjunction with the above mentioned appetizers. Materials and methods: Four groups of 10 mature male rats each were used. The drinking water (DW) containing 5mM of Al2(SO4)3 with 1% glacial acetic acid and/or 10% ethanol made available ad-libidum. Weekly body weight and each other day drinking water volume were measured. Brain and plasma analysis at and Ca were determined from blood obtained by cardiac puncture, in addition to automated complete blood count (CBC), after 10 wks of treatments. Results: The results of plasma Al levels indicated that, the addition of acetic acid or ethanol to Al containing drinking water enhanced significantly its absorption and even more when combined relative to control. This enhancement was evident as well in increased Al and Ca deposited in the brain while no change in plasma Ca. The CBC results showed highly significant thombocytopnia for the 1st time, in addition to microcytosis and hypochromia. Evidently, thrombocytopoietin synthesis, and/or action is blocked by Al from acting on the cellularity of bone marrow. Conclusion: The addition of acetic acid and/ or 10% ethanol to Al containing drinking solution enhanced Al absorption when acid is used and an addative effect when both are used. The toxic plasma level caused hypochromia, microcytosis and severe thrombocytopenia in addition to brain atrophy.